Trading Caterpillar Fungus in Tibet : When Economic Boom Hits Rural Area - Sulek, Emilia Roza (Book collections on Project MUSE., 2019)
Caterpillar fungus, often called the Himalayan Viagra, is a subject of the latest commodity boom which changed the economic fates of Tibetan pastoralists in China. This expensive medicinal resource made a spectacular market career in East Asia after the outbreak of avian influenza and SARS. Growing demand for this 'wonder drug' created for people on the Tibetan plateau where this fungus is endemic attractive income opportunities which they never had before. Tibetan pastoralists engaged in this new 'gold rush' and turned from subsistence-oriented yak and sheep breeders living in a cash-poor environment into local economic elite. This book tells a story of successful pastoralists high on the Tibetan plateau who take advantage of the economic boom in the Chinese market to accomplish their own goals. They emerge as far more sophisticated actors than most outsiders would give credit to before reading this book.